The Effect of Problem Based Learning (PBL) and Cognitive Ability on Learning Outcomes of Sprint Running in Students of SMP Negeri 8 Tasikmalaya - Arif Rahman Hakim; Ayi Suherman; Anggi Setia Lengkana; Sri Maryati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine: (1) differences in learning outcomes for students who are taught by PBL and direct teaching methods, low and high cognitive abilities. (2) the interaction between learning methods and cognitive abilities on learning outcomes of sprints. (3) differences in learning outcomes of sprinting with the PBL and direct teaching methods in terms of high cognitive ability. (4) the difference in learning outcomes of sprinting with the PBL and direct teaching methods in terms of low cognitive ability. This research is a quasi-experimental research with a factorial design. The research sample was taken using random sampling technique, the number of samples used was 50 students of SMP Negeri 8 Tasikmalaya. Analysis of the data used is the requirements test and hypothesis testing. The results of the study show: (1) there are differences in learning outcomes between students taught by PBL and direct teaching methods, (2) there is an interaction between learning methods and cognitive abilities on learning outcomes of sprints. (3) there are differences in learning outcomes between students who are given learning using the PBL Model and the Direct Instruction Model in groups of students who have high cognitive, (4) there is no difference in the learning outcomes of sprints between students who are given learning using the PBL Model and the Direct Instruction Model in groups of students who have low cognitive abilities.